2016
DOI: 10.5380/avs.v21i2.40245
|View full text |Cite
|
Sign up to set email alerts
|

Transferência De Resistência Antimicrobiana Entre Enterobactérias Patogênicas De Importância Aviária - Impactos Em Saúde Pública

Abstract: Ligações entre o uso indiscriminado de antimicrobianos na produção de animais, que se destinam à alimentação humana, conferindo pressão seletiva sobre microrganismos, e uma emergência na sua existência, surgimento, disseminação e transferência de genes que conferem de resistência a drogas antimicrobianas constituí preocupação global crescente. Processos de resistência antimicrobiana ocorrem de modo natural ou adquirido, sendo a maneira adquirida a mais preocupante. Vários são os mecanismos de transferência de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…According to the results, the resellers sold several animal species, with 8.3% (5/60) of them housing only the species Gallus gallus domesticus and 91.7% (55/60) housing chickens and other species of birds and mammals. The existence of different species of animals at these resellers is worrying because of the possibility of them harboring pathogenic bacteria in the intestinal tract such as Salmonella spp., Campylobacter spp., Escherichia coli, among others, constituting potential reservoirs of zoonotic diseases of importance in human and veterinary medicine (2,8) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the results, the resellers sold several animal species, with 8.3% (5/60) of them housing only the species Gallus gallus domesticus and 91.7% (55/60) housing chickens and other species of birds and mammals. The existence of different species of animals at these resellers is worrying because of the possibility of them harboring pathogenic bacteria in the intestinal tract such as Salmonella spp., Campylobacter spp., Escherichia coli, among others, constituting potential reservoirs of zoonotic diseases of importance in human and veterinary medicine (2,8) .…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the agent can still survive in different environments and pose a risk of resistance transfer and spread to commensal bacteria. These risks were pointed out by Chantziaras et al (27) , who correlated antimicrobial resistance in food-producing animals, such as birds, with humans; and by Silva et al (2) , who showed evidence that the intestinal microbiota of birds can harbor zoonotic bacteria-pathogenic or not-that can be reservoirs of genes that confer resistance to antimicrobials, thus playing an important role in the spread of bacterial resistance among different animal species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations